Pyridino-18-crown-6 ether type chemosensors containing a benzothiazole fluorophore unit: Synthesis and enantiomeric recognition studies. Issue 20 (17th May 2019) - Pál, Dávid; Móczár, Ildikó; Szemenyei, Balázs; Marczona, Dániel; Kocsis, Ivett; Prikler, Gergely; Vezse, Panna; Baranyai, Péter; Huszthy, Péter
Abstract: Three new fluorescent enantiopure pyridino-18-crown-6 ethers containing a benzothiazole unit were prepared, and the enantiomeric discrimination of these sensor molecules toward the hydrogen perchlorate salts of 1-phenylethylamine, 1-(1-naphthyl)ethylamine, phenylglycine methyl ester and phenylalanine methyl ester was studied in acetonitrile by fluorescence spectroscopy. The ligands revealed appreciable or moderate selectivity toward the enantiomers of hydrogen perchlorate salts of 1-phenylethylamine, 1-(1-naphthyl)ethylamine and phenylglycine methyl ester. Graphical abstract: Image 1